2022
DOI: 10.3390/ijerph191811341
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Burnout at University: The Role of Gender and Worker Status

Abstract: Students’ burnout has been widely investigated in recent decades, mainly showing a higher risk for female students across academic levels. To our knowledge, few studies have investigated whether employed students experience higher academic burnout risks. In this regard, previous findings have shown mixed results. The current study investigated the differences in burnout experience based on students’ gender and worker status. We expected to find differences among study groups in their burnout levels. The partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 91 publications
2
14
0
5
Order By: Relevance
“…40,41 Our results were similar to previous studies' findings that, in general, female students report more exhausted than their male counterparts. 10,13,[42][43][44][45][46] The COVID-19 pandemic shifted students' priorities, some of the changes in behavior were the result of mandatory requirements (such as: increased hand washing, lockdowns, mandatory mask wearing), many were worried about their own health, health of their families, or struggling financially, perhaps making them less focused on academics, and increasing academic difficulties. It is possible that in circumstances surrounding COVID-19 pandemic female students were more exhausted, which can be related to the environment, where the activities were no longer what they used to be, because in addition to developing academic activities, the female students had to carry out other possibly increase the domestic activities (cleaning, cooking, washing, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Our results were similar to previous studies' findings that, in general, female students report more exhausted than their male counterparts. 10,13,[42][43][44][45][46] The COVID-19 pandemic shifted students' priorities, some of the changes in behavior were the result of mandatory requirements (such as: increased hand washing, lockdowns, mandatory mask wearing), many were worried about their own health, health of their families, or struggling financially, perhaps making them less focused on academics, and increasing academic difficulties. It is possible that in circumstances surrounding COVID-19 pandemic female students were more exhausted, which can be related to the environment, where the activities were no longer what they used to be, because in addition to developing academic activities, the female students had to carry out other possibly increase the domestic activities (cleaning, cooking, washing, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In students, a common reason for fatigue might simply be an excessive academic workload, which is responsible for the reduction of empathy; this is especially common among medical students [ 12 ]. There is evidences that combining work with studies might also be associated with increased risk of burnout [ 38 ], although the latest findings prove that issue of assessing burnout among working students is much more complicated (with the need to take into consideration also gender as key factor) [ 39 ]. In our research, the more fatigued the students felt (regardless of the reasons for this fatigue), the less empathy they revealed; we also found that students from the medical university were more exhausted, which indicates the statistically significant difference in the intensity of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have confirmed sex differences in burnout experience, with girls to be more prone for developing this syndrome (Tomaszek, Muckacka-Cymerman, 2019). A more recent study revealed that female students score higher in exhaustion, cognitive impairment, and emotional impairment (Fiorilli et al, 2022).…”
Section: Research Focusmentioning
confidence: 95%